Could flavonoid aglycones prevent the absorption of flavonoid glycosides by inhibiting sodium-dependent glucose transporter-1 in the small intestine? - Katrin Sak (Exploration of Drug Science)
Flavonoids present a large group of natural polyphenols with numerous important health benefits for preventing and treating a diverse variety of pathological conditions. However, the actual therapeutic use of these phytochemicals is impeded by their low oral bioavailability. In this commentary article, an interesting paradox is presented: while the ingested flavonoid glycosides can be absorbed by means of sodium-dependent glucose transporters (SGLTs; SGLT1) located in the brush border membrane facing the lumen of the small intestine, certain flavonoid aglycones are able to inhibit these shuttle proteins. It is expected that avoiding the co-intake of such SGLT1 inhibitors concomitantly with flavonoid-rich foods might provide a new option for enhancing the oral bioavailability of flavonoids, thereby preventing the transport of unabsorbed compounds to the large intestine and conversion into catabolites by the colonic microbiota. Altogether, the administration of flavonoids in appropriate combinations is highlighted for getting the maximal health benefits from consuming these bioactive compounds.